Botswana Social Protection Assessment - World Bank (Gaborone, Botswana, 2014)
Botswana is a small, landlocked, upper-middle-income country with a gross domestic product (GDP) of United States (U.S.) 17.3 billion dollars in 2011. Despite high levels of economic growth over the past two decades, poverty and inequality persist in Botswana and unemployment is high. The Government of Botswana (GoB) has developed and approved key strategic documents that articulate its long-term development objectives, including those in the social protection sector. The purpose of this assessment is to inform Botswana's future social protection and labor strategy and policies and help to achieve the goals of vision 2016. The assessment concentrates on social assistance programs as major reforms are already taking place or being considered for active labor market programs (ALMP) and social insurance programs. As social assistance programs are a significant draw on the GoB's budget and revenues from mining are projected to decline over the medium term, it will inevitably be necessary to increase the cost-effectiveness of existing programs. This assessment draws on the World Bank's Africa social protection strategy for 2012-2022 which, in addition to the issues addressed by the overall World Bank social protection strategy, stresses the need to focus on the targeted delivery of social services and on issues of good governance, efficient program design and delivery, and country-driven system development. To meet its objectives, the assessment is organized as follows: chapter one gives a brief discussion of the conceptual framework, chapter two discusses the principal vulnerable groups in Botswana and the risks that they face. Chapter three reviews the principal policies and programs that are already in place to address the risks that have been identified as well as the existing informal social protection arrangements. Chapter four assesses the adequacy of the social protection system by analyzing spending; program coverage, overlaps, and gaps; program generosity; targeting efficiency; cost-effectiveness; incentive compatibility and sustainability; monitoring and evaluation; and institutional arrangements. Chapter five contains recommendations.